dtan5457
  • dtan5457
pre calc question
Mathematics
  • Stacey Warren - Expert brainly.com
Hey! We 've verified this expert answer for you, click below to unlock the details :)
SOLVED
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
chestercat
  • chestercat
I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!
dtan5457
  • dtan5457
anonymous
  • anonymous
You want to minimize the TOTAL TIME. Split that into two parts: Tw = walking time. Tr = rowing time. Now make a diagram. He is at M, and wants to reach Q. So he aims the boat at P: | + Q(3,1) | | | P(x,0) -+-------+--*----+-------+----- Coast | 1 2 3 | | | M(0,-2) MP = sqrt(x^2 + 4) PQ = sqrt((x-3)^2 + 1) Row MP in Tr = MP/2 = sqrt(x^2 + 4)/2 Walk PQ in Tw = PQ/4 = sqrt((x-3)^2 + 1)/4 Total time is the sum of those; T = sqrt(x^2 + 4)/2 + sqrt((x-3)^2 + 1)/4 Now do the usual stuff: 2x 2(x - 3) dT/dx = ---------------- + -------------------- 4 sqrt(x^2 + 4) 8 sqrt((x-3)^2 + 1) x (x - 3) dT/dx = ---------------- + -------------------- 2 sqrt(x^2 + 4) 4 sqrt((x-3)^2 + 1) Set that equal to zero: x (x - 3) 0 = ---------------- + -------------------- 2 sqrt(x^2 + 4) 4 sqrt((x-3)^2 + 1) 2x sqrt((x-3)^2 + 1) + (x - 3)sqrt(x^2 + 4) 0 = ----------------------------------------... 4 sqrt(x^2 + 4) sqrt((x-3)^2 + 1) Set the top to zero: 2x sqrt((x-3)^2 + 1) + (x - 3)sqrt(x^2 + 4) = 0 2x sqrt((x-3)^2 + 1) = (3 - x)sqrt(x^2 + 4) Square both sides: 4x^2((x - 3)^2 + 1) = (9 - 6x + x^2)(x^2 + 4) 4x^2(x^2 - 6x + 9 + 1) = (9 - 6x + x^2)(x^2 + 4) 4x^4 - 24x^3 + 40x^2 = 9x^2 - 6x^3 + x^4 + 36 - 24x + 4x^2 3x^4 - 18x^3 + 27x^2 = + 36 - 24x 3x^4 - 18x^3 + 27x^2 + 24x - 36 = 0 x^4 - 6x^3 + 9x^2 + 8x - 12 = 0 x = 1 is an obvious solution: 1 - 6 9 8 - 12 (1) 1 -5 4 12 ------------------------ 1 - 5 4 12 zero x^3 - 5x^2 + 4x + 12 = 0 is the reduced equation. A quick-and-dirty graph of x^3 - 5x^2 + 4x + 12 shows only a root for a negative number. So x = 1 is the solution
Here_to_Help15
  • Here_to_Help15
https://answers.yahoo.com/question/index?qid=20130403135357AAHZFha

Looking for something else?

Not the answer you are looking for? Search for more explanations.